A mechanistic study of the interaction of water-soluble borate glass with apatite-bound heterocyclic nitrogen-containing bisphosphonates. (February 2016) - Pramanik, Chandrani; Sood, Parveen; Niu, Li-na; Yuan, He; Ghoshal, Sushanta; Henderson, Walter; Liu, Yaodong; Jang, Seung Soon; Kumar, Satish; Pashley, David H.; Tay, Franklin R.
Graphical abstract: Abstract: Long-term oral and intravenous use of nitrogen-containing bisphosphonates (N-BPs) is associated with osteonecrosis of the jaw. Although N-BPs bind strongly to bone surfaces via non-covalent bonds, it is possible for extrinsic ions to dissociate bound N-BPs from mineralized bone by competitive desorption. Here, we investigate the effects and mechanism of using an ionic cocktail derived from borate bioactive glass for sequestration of heterocyclic N-BPs bound to apatite. By employing solid-state and solution-state analytical techniques, we confirmed that sequestration of N-BPs from bisphosphonate-bound apatite occurs in the presence of the borate-containing ionic cocktail. Simulations by density functional theory computations indicate that magnesium cation and borate anion are well within the extent of the risedronate or zoledronate anion to form precipitate complexes. The sequestration mechanism is due to the borate anion competing with bisphosphonates for similar electron-deficient sites on the apatite surface for binding. Thus, application of the borate-containing ionic cocktail represents a new topical lavage approach for removing apatite-bound heterocyclic N-BPs from exposed necrotic bone in bisphosphonate-related osteonecrosis of the jaw. Statement of significance: Long-term oral consumption and injections of nitrogen-containing bisphosphonates (N-BPs) may result in death of the jaw bone when there is traumatic injury to the bone tissues. To date, there is no effective treatment for such a condition. This work reported the use of an ionic cocktail derived from water-soluble borate glass microfibers to displace the most potent type of N-BPs that are bound strongly to the mineral component on bone surfaces. The mechanism responsible for such an effect has been identified to be cation-mediated complexation of borate anions with negatively-charged N-BPs, allowing them to be released from the mineral surface. This borate-containing cocktail may be developed into a novel topical rinse for removing mineral-bound N-BPs from exposed dead bone.